Christian inculturation in India - Collins, Paul M. (Aldershot, England ; Burlington, VT : Ashgate, 2007)
Drawing together international and Indian sources, and new research on the ground in South India, this book presents a unique examination of the inculturation of Christian Worship in India. Paul Collins examines the imperatives underlying the processes of inculturation - the dynamic relationship between the Christian message and cultures, and then explores the outcomes of those processes in terms of architecture, liturgy and ritual and the critique offered of these outcomes, especially by Dalit theologians.
Cultures, commerce and colonies : the export factor -- Setting the scene -- Redefining identities : landscapes and imperatives to 1963 -- Whose values; which cultures? : the effects of local theologies -- Art, architecture and topography : temples and churches in South India -- Rites and rituals : lex orandi, lex credendi? -- Imperatives for a new agenda.
Includes bibliographical references (p. [211]-225) and indexes.
Keywords: Christianity and culture -- India; Christianity -- India; Christianity and culture; Electronic books